(3GdJegjO deG aj GdehWC ef GdeYGfi hGdCSGfjOs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3jHOC HMOjK NGeS hGQHYjf dfGaY Yf GHf YeQ s
(3BNQgG (B:s
(3jfJgi HMOjK QGHY hYTQjf dYHOGddg Hf OjR Yf SdjeGf Hf jSGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1907 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B484s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(347) s
Keywords: (3GdMOjK h GdeUWdMs